Brodcast television in Brazil: concentration of ownership and the lack of communication policies - Demarchi, Carlos Henrique [UNESP] (Univ Taubate, 2015)
Created more than 60 years ago, broadcast television now reaches most of brazilian households. Over the decades, however, media broadcasting has been consolidated with the predominance of commercial channels and the concentration of media ownership in the hands of a few companies. The laws concerning the matter are too old and organised civil society demands new regulation. A whole chapter of the 1988 Brazilian Constitution was dedicated to Communication and has established that media broadcasting must have cultural and educative goals, as well as prioritize regional and independent content production and base itself in the complementarity of public, private and state systems. Based on a bibliographical research, this paper aims to analyze brazilian broadcast television regarding its inauguration and expansion processes, the set of norms and standards that governs it, the lack of public policies for mass communication and the contemporary discussion regarding its opening for new social actors. Our conclusions show that beyond the need for updating the legislation there is a lack of public intervention in order to ensure greater social participation, as well as the supervision of the broadcasters' operations.
Keywords: Broadcast Television; Communication Policies; Concentration of Media Ownership